The Effectiveness of Interaction between Scientific Supervisors and Graduate Students at the University and at the Academy of Sciences - E. V. Biricheva; Z. A. Fattakhova (Высшее образование в России)
The effectiveness of work and relationship of postgraduate students with their supervisors seem to be an urgent issue in the context of contemporary transformations of the Russian system of training highly qualified personnel. The article assesses the understanding of the purposes of graduate school by both “sides”, the specifics of the interaction between mentors and their mentees, the leading difficulties and ways to overcome them. Since in our country postgraduate programs are implemented not only at universities, we also compared situations at a university and in an academic community considering the case of the Ural Federal University (UrFU) and scientific institutes of the Ural Branch of the Russian Academy of Sciences (UB RAS). Empirical methods for collecting initial data were applied both at UrFU and at UB RAS and included interviewing scientific leaders and questioning graduate students. A series of in-depth interviews with mentors led to the formulation of research hypotheses and allowed the elaboration of an online questionnaire for graduate students. As a result, we may state the prevalence of the “external” obstacles that reduce the effectiveness of the interaction of young scientists with their scientific leaders; in general, the relationship between them looks quite harmoniously. Among the most pressing problems we have identified (1) disorientation about the concept of postgraduate studies without obligatory defense of the thesis (especially at university); (2) low productivity of the “educational” postgraduate studies; (3) lack of advanced training for supervisors in the field of management in science; (4) high employment of professors; (5) side mentoring and (6) the lack of plans for writing a dissertation. The solution of this set of problems seems to be based, first of all, on a new regulatory framework at the federal level, revising the types and volumes of workload of graduate students and their supervisors, fixing the need to write a dissertation during the course of study, regulating the requirements for scientific supervisors and guaranteeing them advanced training in the field managerial competencies. The positive practice of employing all graduate students at academic institutions, at least for a fraction of the rate, may also help universities in increasing the motivation of graduate students to defend their PhD thesis and build their future career at the university.